Implant Plane Does Not Seem to Impact Shoulder Function after Direct-to-Implant Breast Reconstruction in Non-Radiated Patients: A Randomized Controlled Trial - von Buchwald, Signe; Dyrberg, Diana Lydia; Dalaei, Farima; Sørensen, Jens Ahm; Thomsen, Jørn Bo (Archives of Plastic Surgery, 2025)
Subpectoral implant placement in breast reconstruction has been associated with potential shoulder function impairment compared to prepectoral placement, though the evidence remains inconclusive. This study aimed to investigate differences in shoulder function following mastectomy and direct-to-implant breast reconstruction using prepectoral or subpectoral implant placement.Forty-two women aged 18 years or older, eligible for direct-to-implant breast reconstruction, were randomized 1:1 to undergo either prepectoral or subpectoral implant placement. Data were collected at baseline and at 3- and 12-month follow-ups. Shoulder function was assessed using the validated Constant Shoulder Score (CSS), which evaluates pain, activities of daily living, range of motion, and strength. Pectoralis major muscle (PMM) strength was also measured.Baseline and demographic characteristics were comparable between the groups. No differences were observed in total CSS or the modified CSS (including the PMM strength) between the prepectoral and subpectoral groups at baseline or at the 3- and 12-month follow-ups. At 12 months, total CSS (p = 0.74) and modified CSS (p = 0.45) remained similar across both groups.There were no significant differences in shoulder and arm function between the sub- and prepectoral reconstruction groups. These findings suggest that concerns regarding shoulder function should not dictate the choice of implant placement plane in direct-to-implant breast reconstruction.
Keywords: impaired shoulder function; functional assessment; subpectoral implant placement; prepectoral implant placement; direct-to-implant reconstruction